The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.neuro.2018.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Selective dopaminergic neurotoxicity of three heterocyclic amine subclasses in primary rat midbrain neurons

Abstract: Heterocyclic amines (HCAs) are primarily produced during high temperature meat cooking. These compounds have been intensively investigated as mutagens and carcinogens. However, converging data suggest that HCAs may also be neurotoxic and potentially relevant to neurodegenerative diseases such as Parkinson's disease (PD). The identification of new potential etiological factors is important because most PD cases are sporadic. Our group previously showed that 2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 51 publications
1
31
0
Order By: Relevance
“…These products can participate in a Maillard reaction to generate heterocyclic aromatic amines (HAAs) [ 9 ] and advanced glycation end products (AGEs). It has been reported that high HAA intake is associated with a variety of acute diseases, such as nonalcoholic fatty liver disease and neuronal damage [ 10 , 11 ]. Excessive intake of AGE will result in their accumulation in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…These products can participate in a Maillard reaction to generate heterocyclic aromatic amines (HAAs) [ 9 ] and advanced glycation end products (AGEs). It has been reported that high HAA intake is associated with a variety of acute diseases, such as nonalcoholic fatty liver disease and neuronal damage [ 10 , 11 ]. Excessive intake of AGE will result in their accumulation in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…They structurally resemble the Parkinson’s disease (PD) causing substance 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) and showed neurotoxic effects on dopaminergic neurons, especially as methylated forms (e.g. 2,9-dimethyl-β-carbolinium ion [2,9-dime-BC +]) (Hamann et al 2006 ; Neafsey et al 1995 ; Cruz-Hernandez et al 2018 ; Sammi et al 2018 ). Inhibition of the complex I of the respiratory chain, induction of apoptosis and activation of microglia are the main compounds of this toxic effects of 2,9-dime-BC + (Ostergren et al 2006 ; Polanski et al 2010 ; Hamann et al 2006 ; Hans et al 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…It may be postulated that the inhibition of OCTs by HAAs may block the transport of endogenous OCT substrates, especially that of catecholamines, known to act as neurotransmitters. By this way, OCT inhibition may contribute to the possible neurotoxicity of HAAs, including PhIP, Trp-P-1 and Trp-P-2 (Cruz-Hernandez et al, 2018;Naoi et al, 1989). In particular, OCT inhibition by harmane and norharmane may be involved in the neurological diseases thought to be promoted by these two HAAs, such as essential tremor and the Parkinson disease (Esmaeili et al, 2012;Lavita et al, 2016).…”
Section: Discussionmentioning
confidence: 99%